2018
DOI: 10.29271/jcpsp.2018.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Remission Rate Of Acute Lymphoblastic Leukemia (all) In Adolescents And Young Adults (aya)

Abstract: The remission induction rate was 70.7% in the adolescents and young adults with acute lymphoblastic leukemia at the study centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Acute lymphoblastic leukemia, although the most common hematologic neoplasm in children, is less common in adolescents and adults and has a survival rate of 20% to 40. [11][12][13] Symptoms of the disease are nonspecific and often include fever, fatigue, bruising and bleeding due to thrombocytopenia and infection due to neutropenia, but other symptoms include hepatomegaly and splenomegaly and joint pain. However, the occurrence of cholestatic jaundice in this disease and as one of the early manifestations is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia, although the most common hematologic neoplasm in children, is less common in adolescents and adults and has a survival rate of 20% to 40. [11][12][13] Symptoms of the disease are nonspecific and often include fever, fatigue, bruising and bleeding due to thrombocytopenia and infection due to neutropenia, but other symptoms include hepatomegaly and splenomegaly and joint pain. However, the occurrence of cholestatic jaundice in this disease and as one of the early manifestations is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Using Open-Epi software for sample size calculation, a sample size of 84 was selected to represent the true population based on the anticipated proportion of 70% remission in ALL cases, keeping a 95% confidence level and 6% absolute precision due to feasibility issues. 3 A total of 84 diagnosed patients of Acute lymphoblastic leukemia (ALL) undergoing induction of remission were included. The diagnosis in all these patients was based on cytological including Giemsa stained peripheral blood smear, bone marrow aspirate smears, and trephine biopsy, immune-phenotypic and cytogenetic criteria.…”
Section: Methodsmentioning
confidence: 99%
“…A local study covering Sindh province reported 70% remission in pediatric age. 3 Regarding remission, literature has reported the clinical significance of hematological markers (reticulocyte count, ANC, and platelet) to predict remission in cases of ALL. A regular increase in trends of using these markers has dramatically decreased the frequencies of invasive procedures like bone marrow aspiration and trephine.…”
Section: Introductionmentioning
confidence: 99%
“…As a malignant hematological condition, adult B-cell acute lymphoblastic leukemia (B-ALL) is caused by the abnormal proliferation of B-lymphocyte lineage precursor cells in the bone marrow. Studies have shown that complete remission is achievable in most patients with B-ALL after receiving induction chemotherapy [ 1 , 2 ]. However, the recurrence, drug resistance and extramedullary infiltration during treatment remain the chief reasons for the poor efficacy in B-ALL patients, and the long-term efficacy is not optimistic [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%